GESTÃO DO CONHECIMENTO E A MOTIVAÇÃO NA MELHORIA DA PRESTAÇÃO DE SERVIÇOS - Brochier, Hélio Luiz (Revista Liberato, 2013)
This report is presented with the objective of softening the financiall crisis and the quality of the services and the difficulties of their high staff and/or their personal resources Management and its relationship with the administration and personal developinent. The report shows the importance, of the motivacional indicators and training, for the imporvement, of the services and the employees and customers satisfaction. A bibliographical review was accomplished about management of human resources and its evolution in administrative theories, tendencies and perspectives, management, education and work, of the quality. The focus is the motivational indicators, tranining. We report a study checked the level of the emplyees motivation and satisfaction in their jobs and work in Hospital, the turn over, employces absence, hours of training, the internements, the patients complaints, and satisfaction with the services offered by the Hospital and for the operator Unimed. The data were tabulated and and, then analysed with the reference of the bibliography, in which we can be inferred that the motivation, training are indicators that contribute to the employees and customers satisfacion as well as for the improvement of the services. Based on the results obtained in this particular study, in the bibliography and in the experience already acomplished by some organizations, we presente suggestions and contributions, in order to aid Managers of hospitals and human resources in the elaboration of the plan of a personal politic development, because we believe the investment in people and its knowledge, the largest differential that a company can have in the competitive market, through the public recognition.